Analisis Nilai-Nilai Pendidikan Akhlak dalam Novel Kembara Rindu Karya Habiburrahman El-Shirazy - Annisa Julita (UNISBA Press, 2022)
Abstract. Moral problems are problems for which there is no complete answer. Parameters of declining morals are marked by rampant juvenile delinquency, corruption, collusion, nepotism, promiscuity, bullying etc. It is necessary to takesteps preventive that must be done. Education has the most strategic position in teaching morals. the provision of moral education is not only in the form of verbal in formal or non-formal education, but can also be through written works presented in the form of literature or fiction writings such as novels. When reading a novel indirectly, it means that the reader is in the process of receiving messages, in this case educational messages. This study aims to describe the views of novel critics about the novel Kembara Rindu, the values ​​of moral education in the novel Kembara Rindu by Habiburrahman El-Shirazy, and the relevance of the values ​​of moral education in the novel Kembara Rindu by Habiburrahman El-Shirazy to PAI learning materials. The type of research used is library research with a qualitative approach, using data collection techniques through documentation. The researcher as a human instrument has a function as a data source, collecting data to making conclusions on everything that has been found. The data analysis technique used is content analysis (content analysis). The results of this study indicate that the views of the critics of the novel call this novel as a soul builder and insert a lot of advice and da'wah and there are many meanings and lessons that can be taken. The novel also contains the values ​​of moral education, including praying, being grateful, being honest, respecting parents, caring, respecting teachers, being responsible, and being patient. Then there is the relevance of the moral content in the novel Kembara Rindu with Islamic religious education learning materials, including faith, morals, worship, and the Qur'an. Abstrak. Problematika akhlak merupakan persoalan yang belum ada jawabannya secara tuntas. Parameter merosotnya akhlak ditandai dengan maraknya kenakalan remaja, korupsi, kolusi, nepotisme, pergaulan bebas, bullying dan sebagainya. Perlu adanya langkah preventif yang harus dilakukan. Pendidikan memiliki posisi paling strategis dalam pengajaran akhlak. pemberian pendidikan akhlak tidak hanya dalam bentuk verbal pada pendidikan formal ataupun nonformal, tetapi dapat juga melalui karya tulis yang disajikan berupa sastra maupun tulisan-tulisan fiksi seperti Novel. Saat membaca novel secara tidak langsung, berarti pembaca sedang melakukan proses penerimaan pesan, dalam hal ini pesan-pesan pendidikan. Penelitian ini bertujuan untuk mendeskripsikan pandangan para kritik novel tentang novel Kembara Rindu, nilai-nilai pendidikan akhlak dalam novel Kembara Rindu karya Habiburrahman El-Shirazy, serta relevansi nilai-nilai pendidikan akhlak dalam novel Kembara Rindu karya Habiburrahman El-Shirazy terhadap materi pembelajaran PAI. Jenis penelitian yang diguanakan yaitu library research dengan pendekatan kualitatif, menggunakan teknik pengumpulan data melalui dokumentasi. Peneliti sebagai human instrumen yang memiliki fungsi sebagai sumber data, pengumpulan data hingga membuat kesimpulan atas semua yang telah ditemukan. Teknik analisis data yang digunakan analisis isi (content analysis). Hasil penelitian ini menunjukkan pandangan para kritik novel menyebut novel ini sebagai pembangun jiwa serta banyak menyisipkan nasihat serta dakwah dan terdapat banyak makna serta pelajaran yang dapat diambil. Dalam novel tersebut juga terkandung nilai-nilai pendidikan akhlak, diantaranya berdoa, bersyukur, jujur, menghormati orang tua, peduli, menghormati guru, tanggung jawab, dan sabar. Kemudian adanya relevansi dari kandungan akhlak dalam novel Kembara Rindu dengan materi pembelajaran pendidikan agama Islam, diantaranya keimanan, akhlak (budi pekerti), ibadah, dan Al-Qur’an..